(3eYQaI GdCSWQdGHs - (3YHO GdQMef Hf YeQ Hf Sgd GdUhaj GdQGRqj, CHh GdMSjf,J (B376 (3g` s ((3TGg Hf YHO Gddg s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Sec GdSeGA HbOQJg GdebGdI GdChdi hgj NeShf HGHkG C (B: (3ai ebOeI jMJGL EdjgG HUaI gPg GdBdI s
(3BNQgG (B:s
(3aeG NQL agh GdPi Hjf WdhY GdaLQ hHjf eZjH GdTeS ai CbUQ jhe ai GdSfI JeJ GdebGdI GdKGdK HJeGe LejY GdcJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B162s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B253 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B398 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs